Outcome in paraplegic dogs with or without pain perception due to thoracolumbar fibrocartilaginous embolic myelopathy or acute non-compressive nucleus pulposus extrusion - Togawa, Go; Lewis, Melissa J.; Devathasan, Dillon (Frontiers in Veterinary Science, 2024)
Fibrocartilaginous embolic myelopathy (FCEM) and acute non-compressive nucleus pulposus extrusion (ANNPE) are common causes of acute spinal cord injury in dogs. Outcome among paraplegic deep pain positive (DPP) and deep pain negative (DPN) dogs with either condition and factors influencing recovery have not been clearly established. Dogs with thoracolumbar FCEM or ANNPE resulting in paraplegia presenting to university hospitals between 2012–2022 were retrospectively included. Diagnosis of FCEM or ANNPE was based on clinical and magnetic resonance imaging findings. Outcome was defined as successful (recovery of independent ambulation) or unsuccessful (non-ambulatory ≥ 3 months following diagnosis or at the time of death/euthanasia). Logistic regression analysis was performed to investigate associations between clinical or imaging variables and outcome. Thirty-one dogs were included. Fourteen dogs were initially paraplegic DPP (8 FCEM, 6 ANNPE) and 17 dogs were paraplegic DPN (11 FCEM, 6 ANNPE). Outcome was available for 26 dogs (14 DPP, 12 DPN) with a median follow-up time of 182 days (range, 0–2311) including 2 dogs euthanized at the time of diagnosis; 1/12 DPN dogs (8.3%) regained independent ambulation, whereas 9/14 DPP dogs (64.3%) regained independent ambulation. DPN dogs had a significantly higher risk of not regaining independent ambulation compared to DPP dogs (OR: 47.40, 95% CI: 2.09–1073.99). No other variables were associated with outcome. While recovery of ambulation was possible, these results confirm that absence of pain perception is a useful negative prognostic indicator in dogs with severe thoracolumbar FCEM or ANNPE.